DAMPAK ALIH FUNGSI LAHAN TERHADAP PERUBAHAN MATA PENCAHARIAN PETANI DI DESA BAYU KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR - Arza, Ibnu Khattab; Zalmita, Novia (Jurnal Pendidikan Geosfer, 2024)
The conversion of agricultural land functions affects people's livelihoods in Bayu Village, Darul Imarah, Aceh Besar. This study examines the impact of land conversion on changes in the livelihoods of farmers in Bayu Village, Darul Imarah, Aceh Besar. The study aimed to describe the impact of the conversion of agricultural land from 2021 to 2023 into roads, shopping locations, and residential complex land in Bayu, Darul Imarah, Aceh Besar. This research was conducted in June 2023. The used qualitative descriptive methode. The data collection technique is carried out using; (1) observation techniques, (2) document analysis, and (3) interview. The results of this study (1) the loss of opportunities for some farmers, (2) changes in livelihoods for some farmers.